2021
DOI: 10.1200/jco.20.02063
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Risk Tool for Predicting Severe Toxicity in Older Adults Receiving Chemotherapy for Early-Stage Breast Cancer

Abstract: PURPOSE Limited tools exist to predict the risk of chemotherapy toxicity in older adults with early-stage breast cancer. METHODS Patients of age ≥ 65 years with stage I-III breast cancer from 16 institutions treated with neoadjuvant or adjuvant chemotherapy were prospectively evaluated for geriatric and clinical features predictive of grade 3-5 chemotherapy toxicity. Logistic regression with best-subsets selection was used to identify and incorporate independent predictors of toxicity into a model with weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 39 publications
1
61
1
2
Order By: Relevance
“…Though the benefits and tolerability of endocrine therapy does not depend on age, research has shown chemotherapy tolerability decreases with age [ 28 , 29 ]. The recent 2021 Cancer and Aging Research Group-Breast Cancer (CARG-BC) score has been developed as a risk calculation tool to predict chemotherapy toxicity in treatment of early stage breast cancer in the elderly; the goal is to make chemotherapy a safer and more accessible treatment option in this group [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the benefits and tolerability of endocrine therapy does not depend on age, research has shown chemotherapy tolerability decreases with age [ 28 , 29 ]. The recent 2021 Cancer and Aging Research Group-Breast Cancer (CARG-BC) score has been developed as a risk calculation tool to predict chemotherapy toxicity in treatment of early stage breast cancer in the elderly; the goal is to make chemotherapy a safer and more accessible treatment option in this group [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Elderly women with breast cancer have significantly better overall and cancer-specific survival when they received surgery, and surgery is the most important factor associated with better survival, moreso than age, stage, and ER/PR/HER2 status [29] . Despite this, research has shown that the elderly are less likely to undergo surgery for breast cancer [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive geriatric-assessment (CGA) screening tools for older patients can be useful for predicting severe AE [27], and it is important to intensify supportive care and develop modi ed treatment regimens in vulnerable patients who may subsequently experience greater toxicity [28]. For the RCT group, we developed a CGA screening tool at baseline and at each point to analyze the relationship between AEs and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the Cancer and Aging Research Group-Breast Cancer score was validated to predict grade 3–5 chemotherapy toxicity in older adults with early-stage breast cancer. 95 Among the eight predictors of toxicity, limited mobility and insufficient social support were both identified as important parameters. These findings further highlight that, in the setting of escalating therapy to include chemotherapy, clinicians should consider a comprehensive geriatric assessment before starting treatment.…”
Section: Clinical Trends In De-implementation In Low-risk Breast Cancer In Older Womenmentioning
confidence: 98%